2022
DOI: 10.1128/msystems.00469-22
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiota from Periodontitis Promote Oral Squamous Cell Carcinoma Development via γδ T Cell Activation

Abstract: The work reveals the role of the oral microbiota from periodontitis in carcinogenesis. Furthermore, our study provides insight into the pathogenesis of OSCC with periodontitis by outlining the tumor-associated immune response shaped by the oral microbiota from periodontitis, which might identify new research and intervention targets for OSCC with periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…In lung tissue, IL 17 expressed by activated γδ T cells could induce macrophage proliferation and M2 polarization, thus further affect disease progression ( 30 , 38 , 39 ). This procedure had been demonstrated in both pulmonary inflammation and lung fibrosis ( 38 , 39 ) as well as in OSCC with periodontitis models ( 35 ). Therefore, does such an immune regulatory mechanism also exist in the COPD disease model and can periodontitis further promote COPD progression by regulating this mechanism?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In lung tissue, IL 17 expressed by activated γδ T cells could induce macrophage proliferation and M2 polarization, thus further affect disease progression ( 30 , 38 , 39 ). This procedure had been demonstrated in both pulmonary inflammation and lung fibrosis ( 38 , 39 ) as well as in OSCC with periodontitis models ( 35 ). Therefore, does such an immune regulatory mechanism also exist in the COPD disease model and can periodontitis further promote COPD progression by regulating this mechanism?…”
Section: Discussionmentioning
confidence: 99%
“…For the bacteria-cell co-culture experiments, the bacteria were centrifuged and resuspended in 10% fetal bovine serum (FBS) containing DMEM. The bacteria were then co-cultured with cells at a multiplicity of infection (MOI) of 100 ( 35 , 73 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study revealed that C. albicans promoted OSCC development via the IL-17A/IL-17RA-macrophage axis, and the tumor-associated macrophages (TAMs) attracted by C. albicans infection polarized into the M2 phenotype with high expression of PD-L1 [ 11 ]. Another study demonstrated that periodontitis-associated oral microbiota could activate IL-17-positive δγ T cells and promote OSCC development and that activated δγT cells were necessary for the IL-17/signal transducer and promoted M2 macrophage infiltration in OSCC proliferation [ 21 ]. Researchers have reported that Prevotella activates TLR2, leading to the production of Th17-polarizing cytokines, including IL-23 and IL-1.…”
Section: Discussionmentioning
confidence: 99%
“…However, the neutralisation of γδT cells further boosted the overgrowth of Ascomycota in the gut. It is worth mentioning that microbiota-related IL-17A producing γδT cells were reported to promote OC and colorectal cancers (Reis et al 2022 ; Wei et al 2022 ). That’s to say, γδT cells may be important parts in maintaining microbial homoeostasis, the abnormality of which may promote cancer development.…”
Section: Discussionmentioning
confidence: 99%